KETIDAKPASTIAN EKONOMI TERHADAP STABILITAS BANK DI INDONESIA - Andre Berto; Liza Handoko (Taksasila Edukasi Insani, 2025)
The research measures the economic uncertainty variable using World Uncertainty Index (WUI) and uses three proxies of bank risk (bank default risk, bank leverage risk, and bank portfolio risk) to assess its becoming effect on the stability of Indonesia banks. In an analysis based on panel data and a combination of fixed and random effects models, the study aims to reflect how world economic uncertainty influences bank stability in Indonesia. The results however indicate that economic uncertainty shows no influence towards all bank risk aspects, which consists of default risk, leverage risk, and portfolio risk, based on the 5 percent significance level. This result implies that Indonesian banks are generally quite resistant from the direct impact of economic uncertainty relating to credit default risk, leverage risk, and portfolio risk. This research paper also takes into consideration the structural characteristics of banks that would be important predictors of this bank stability risk in these dimensions, namely, loan share, income diversification, liquidity and commission-based income.Keywords : Bank Stability, Economic Uncertainty, Financial Resilience, World Uncertainty Index (WUI)